CONVERGENCE OF GDRP PER CAPITA AND ECONOMIC GROWTH AMONG INDONESIAN PROVINCES, 1988-2008 - Gunawan, Diah Setyorini (Journal of Indonesian Economy and Business, 2011)
In this paper, we analyze the condition among province in Indonesia especially aboutÂ the convergence or divergence in gross domestic regional product. This research usedsecondary data for the 1988-2008 periods. We divide the periods as four episodes, basedÂ on the presidential terms. They are 1988-1999, 1999-2001, 2001-2004, and 2004-2008.Entrophy Theil index, coefficients of variation, Kuznetsâ hypothesis test, absoluteÂ convergence, and conditional convergence were used in this research. This research foundthat the convergence in gross domestic regional product happened in every period of theÂ presidential leadership in Indonesia. We also found that regional economic growth inIndonesia is determined by gross domestic regional product per capita, oil and gasÂ resources, general allocation funds and revenue sharing funds.Keywords: convergence, regional economic growth, gross domestic regional product